Apoptose na resposta inflamatória e nas lesões epiteliais no líquen plano bucal dos tipos reticular e erosivo - Juliana Massote Caldeira Brant (2008)
Oral Lichen Planus (OLP) is a chronic inflammatory disease with different clinical types. Reticular and erosive forms are the most common. Although several aspects are still not completely clear, it is believed that the immunological mechanisms are basic for the initiation and perpetuation of the inflammation in the OLP and that apoptosis mayparticipate in disrupture of the basal layer with the appearance of free keratinocytes. The objective of this study was to approach the role of apoptosis in epithelia and subepitelial infiltrates, in reticular and erosive forms of OLP. Fifteen samples of OLP of each type, reticular and erosive, beyond 10 samples of healthful mucosa were collected and processed.Epithelial thickness and apoptosis in epithelia and in the subepithelial infiltrate was quantified morphometrically, as well as free keratinocytes and the cellularity of the inflammatory infiltrates. TUNEL and M30 CytoDEATH were used for validation of the morphological criteria. Epithelial apoptosis in the erosive OLP was significantly moreintense than in the reticular type and both forms of OLP presented more apoptosis than the healthy oral mucosa. By the other hand, epithelia was thicker in the control than in OLP, and thicker in the reticular form than in the erosive type. Thus, apoptosis seems to participate in the narrowing of the epithelia in reticular and erosive OLP. Apoptosis in the subepithelial infiltrate, opposed to epithelial apoptosis, was more intense in the reticular than in erosive type. Free keratinocytes and inflammatory cellularity infiltrated were more frequent and intense in the erosive than in the reticular type. The more apoptosis in subepitelial infiltrates, the less inflammatory cellularity, the less epithelial apoptosis and the less free keratinocytes.